Adhesive sheet for electronic component transfer and method for processing electronic component using adhesive sheet for electronic component transfer
Patent Information
- Application Number
- JP2024213789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0008】 本発明によれば、電子部品の固定性および剥離性の両方に優れ、当該電子部品が小型·薄型であっても、不具合を防止して、当該電子部品の受け取りおよび受け渡しを可能とする電子部品転写用粘着シートを提供することができる。
Smart Images

Figure 2025023310000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive sheet for transferring electronic components and a method for processing electronic components using the adhesive sheet for transferring electronic components. [Background technology]
[0002] Conventionally, when an electronic component arranged on a specific member is to be transferred to another member, the electronic component is received by an adhesive sheet, and then the electronic component is handed over to the other member. For example, when an LED chip is incorporated into a device, the LED chip formed on the member is once transferred onto an adhesive sheet, and then the LED chip is handed over from the adhesive sheet to a specific device or member, thereby transferring the LED chip.
[0003] As described above, a pressure-sensitive adhesive sheet having an active energy ray curable pressure-sensitive adhesive layer can be used as a pressure-sensitive adhesive sheet for temporarily fixing an electronic component (i.e., receiving an electronic component and then transferring it). Such a pressure-sensitive adhesive sheet can exhibit a predetermined adhesive strength before being irradiated with active energy rays (e.g., ultraviolet rays) and can preferably fix an electronic component, and after being irradiated with active energy rays, the adhesive layer is cured and the adhesive strength is reduced, making it easy to pick up the electronic component.
[0004] In recent years, there is a tendency for miniaturized and thin electronic components to be widely used. Since small and thin electronic components do not have a sufficient contact area with the adhesive sheet and are easily damaged when peeled off, an adhesive sheet having an active energy ray curable adhesive layer that has both fixability and releasability as described above is preferably used. However, particularly in the case of miniaturized and thin electronic components (e.g., 100 μm square or less, 30 μm thick or less), when the electronic components are received and fixed, the electronic components are embedded in the adhesive layer to a high extent, which causes a problem that the electronic components are difficult to peel off and easily damaged even after the adhesive layer is cured. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-53558 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above-mentioned problems in the conventional art, and its object is to provide an adhesive sheet for transferring electronic components, which has excellent both the fixation and releasability of electronic components, and enables the receipt and delivery of the electronic components while preventing defects such as breakage, even if the electronic components are small and thin. [Means for solving the problem]
[0007] The pressure-sensitive adhesive sheet for transferring electronic parts of the present invention comprises a substrate and a pressure-sensitive adhesive layer disposed on at least one side of the substrate, and the pressure-sensitive adhesive layer has a thermal conductivity of 460 mJ / cm 2 The nanoindenter elastic modulus at 25° C. after irradiation with ultraviolet light is 500 MPa or less. In one embodiment, the pressure-sensitive adhesive sheet has a sinking amount of 3 μm to 27 μm in a 40° C. environment using TMA. In one embodiment, the pressure-sensitive adhesive layer has a thickness of 2.1 μm to 35 μm. In one embodiment, the pressure-sensitive adhesive layer has a normal nanoindenter elastic modulus at 25° C. of 0.4 MPa or more. In one embodiment, the pressure-sensitive adhesive layer has a normal probe tack value of 8 N / cm 2 That's all. In one embodiment, the substrate is made of a polyester resin. In one embodiment, the substrate has a thickness of 30 μm to 200 μm. In one embodiment, the electronic component is a mini LED or a micro LED. In one embodiment, the pressure-sensitive adhesive sheet for transferring electronic components includes the pressure-sensitive adhesive layer, the base material, and another pressure-sensitive adhesive layer in this order. According to another aspect of the present invention, there is provided a method for processing electronic components, which uses the above-mentioned adhesive sheet for transferring electronic components, and includes a step a of transferring an electronic component arranged on a first member onto the adhesive layer of the adhesive sheet, and a step b of picking up the electronic component with a second member and peeling the electronic component from the adhesive sheet. In one embodiment, the electronic component is a mini LED or a micro LED. In one embodiment, step b includes step b-1 of contacting the electronic component on the adhesive layer with the second member, step b-2 of irradiating the adhesive sheet with active energy rays, and step b-3 of picking up the electronic component with the second member and peeling the electronic component from the adhesive sheet. In one embodiment, the first member is a sapphire substrate. In one embodiment, the electronic component is a micro LED, and the step a includes irradiating the sapphire substrate on which a plurality of micro LEDs are arranged with UV laser light to transfer the micro LEDs to the adhesive sheet. In one embodiment, a portion of the micro LEDs arranged on the sapphire substrate is selectively transferred to the adhesive sheet. Effect of the Invention
[0008] According to the present invention, it is possible to provide an adhesive sheet for transferring electronic components that has excellent both the fixation and releasability of electronic components, and prevents malfunctions and enables the receipt and delivery of electronic components even if the electronic components are small and thin. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A. Overview of adhesive sheets for transferring electronic components Fig. 1 is a schematic cross-sectional view of an electronic component transfer adhesive sheet according to one embodiment of the present invention. An electronic component transfer adhesive sheet 100 according to this embodiment comprises a substrate 10 and an adhesive layer 20 disposed on at least one side of the substrate 10. Fig. 2 is a schematic cross-sectional view of an adhesive sheet according to another embodiment of the present invention. An adhesive sheet 200 according to this embodiment comprises an adhesive layer 20, the substrate 10, and another adhesive layer 30.
[0011] The adhesive layer 20 contains an active energy ray curable adhesive. The adhesive layer containing the active energy ray curable adhesive is cured and loses adhesive strength when irradiated with active energy rays. The adhesive sheet for transferring electronic components of the present invention (hereinafter also simply referred to as adhesive sheet) has a predetermined adhesive strength before being irradiated with active energy rays, and can preferably fix electronic components, while after being irradiated with active energy rays, the adhesive strength is reduced as described above, and the electronic components can be easily peeled off (transferred).
[0012] The adhesive layer 20 has a compressive strength of 460 mJ / cm 2 The nanoindenter elastic modulus at 25°C after irradiation with ultraviolet light of 100 nm is 500 MPa or less. The nanoindenter elastic modulus refers to the elastic modulus determined from the applied load-indentation depth curve obtained by continuously measuring the load and indentation depth on an indenter when the indenter is pressed into a sample (e.g., an adhesive surface) during loading and unloading. The method for measuring the nanoindenter elastic modulus will be described in detail later. The ultraviolet light irradiation may be performed, for example, using an ultraviolet light irradiation device (manufactured by Nitto Seiki Co., Ltd., product name "UM-810") and ultraviolet light from a high-pressure mercury lamp (characteristic wavelength: 365 nm, accumulated light quantity: 460 mJ / cm2). 2 , Irradiation energy: 70W / cm 2 The adhesive layer is irradiated with UV light (irradiation time: 6.6 seconds).
[0013] In general, when an electronic component is fixed on the adhesive layer, a part (or all) of the electronic component may be embedded in the adhesive layer, thereby exerting a predetermined fixing force. On the other hand, when peeling off the electronic component, the embedding of the electronic component becomes a factor that inhibits the peelability. In the present invention, since the nanoindenter elastic modulus of the adhesive layer after curing is within the above range, it is possible to provide an adhesive sheet that allows the electronic component to be easily peeled off even if the electronic component is partially embedded, since the electronic component has a high degree of freedom of movement in the surface direction on the adhesive layer. By using such an adhesive sheet of the present invention, even when a small and thin electronic component (e.g., a mini LED, a micro LED) is attached, it is possible to peel off the electronic component again without damaging it. In addition, as described above, since the preferable peelability is exerted, sufficient embedding of the electronic component is permitted, and as a result, the adhesive sheet of the present invention is also excellent in the fixation of the electronic component.
[0014] The initial adhesive strength at 23°C when the adhesive layer of the adhesive sheet is attached to a stainless steel plate (SUS304) is preferably 0.1N / 20mm to 30N / 20mm, more preferably 0.1N / 20mm to 15N / 20mm. Within such a range, an adhesive sheet capable of holding electronic components well can be obtained. The adhesive strength is measured in accordance with JIS Z 0237:2000. Specifically, the adhesive sheet is attached to a stainless steel plate (arithmetic mean surface roughness Ra: 50±25nm) by one reciprocation of a 2kg roller, and left at 23°C for 30 minutes, and then peeled off the adhesive sheet under the conditions of a peel angle of 180° and a tensile speed of 300mm / min to measure. The adhesive strength of the adhesive layer changes when irradiated with active energy rays, but in this specification, the "initial adhesive strength" means the adhesive strength before irradiation with active energy rays.
[0015] In one embodiment, the adhesive layer of the adhesive sheet is attached to a stainless steel plate (SUS304), and 460 mJ / cm 2The adhesive strength at 23°C after irradiation with ultraviolet light is preferably 0.01N / 20mm to 0.3N / 20mm, and more preferably 0.02N / 20mm or more and less than 0.2N / 20mm. If it is within such a range, a pressure-sensitive adhesive sheet with excellent releasability can be obtained. The adhesive strength after ultraviolet light irradiation can be measured after attaching the pressure-sensitive adhesive layer to an adherend and then irradiating the adhesive surface with ultraviolet light.
[0016] The thickness of the pressure-sensitive adhesive sheet is preferably from 1 μm to 300 μm, and more preferably from 3 μm to 200 μm.
[0017] The above pressure-sensitive adhesive sheet has a sinking amount in a 40°C environment using a TMA of preferably 2 μm to 35 μm, more preferably 3 μm to 27 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. Within such a range, the electronic components as the adherend are appropriately embedded in the pressure-sensitive adhesive layer, and a pressure-sensitive adhesive sheet excellent in fixation (i.e., receiving ability) and peeling ability (i.e., transferability) can be obtained. The "sinking amount in a 40°C environment using a TMA" refers to the sinking amount after 20 minutes have elapsed since a probe was brought into contact with the pressure-sensitive adhesive layer using a thermomechanical analyzer (TMA). The measurement conditions are probe diameter: 1.0 mm, mode: needle penetration mode, nitrogen gas flow rate: 50.0 ml / min, indentation load: 0.5 N, and measurement atmosphere temperature: 40°C.
[0018] B.Adhesive layer As described above, the pressure-sensitive adhesive layer has a nanoindenter elastic modulus of 500 MPa or less at 25° C. after ultraviolet irradiation. 2 The nanoindenter elastic modulus at 25°C after irradiation with ultraviolet light is more preferably 450 MPa or less, even more preferably 400 MPa or less, particularly preferably 350 MPa or less, and most preferably 300 MPa or less. If it is within such a range, the above-mentioned effect becomes remarkable. In addition, the pressure-sensitive adhesive layer has a modulus of elasticity of 460 mJ / cm 2The nanoindenter elastic modulus at 25°C after irradiation with ultraviolet light is preferably 1 MPa or more, more preferably 5 MPa or more, even more preferably 10 MPa or more, particularly preferably 50 MPa or more, and most preferably 100 MPa or more. Within such a range, a pressure-sensitive adhesive sheet having excellent fixation and capable of transferring electronic components with good positional accuracy can be obtained. The elastic modulus of the pressure-sensitive adhesive layer can be adjusted by any appropriate method, such as the composition of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer, for example, the structure of the polymer contained in the pressure-sensitive adhesive, the type and amount of the crosslinking agent contained in the pressure-sensitive adhesive, etc.
[0019] The normal nanoindenter elastic modulus of the pressure-sensitive adhesive layer at 25°C is preferably 0.1 MPa to 55 MPa, more preferably 0.2 MPa to 40 MPa, even more preferably 0.3 MPa to 30 MPa, and particularly preferably 0.3 MPa to 20 MPa. Within such ranges, a pressure-sensitive adhesive sheet excellent in fixing electronic components can be obtained. The "normal nanoindenter elastic modulus" refers to the elastic modulus before irradiation with active energy rays.
[0020] In one embodiment, the normal nanoindenter elastic modulus of the pressure-sensitive adhesive layer at 25° C. is preferably 10 MPa or less, more preferably 8 MPa or less, and even more preferably 3 MPa or less. Within such a range, a pressure-sensitive adhesive sheet that is particularly excellent in fixing electronic components can be obtained.
[0021] In another embodiment, the normal nanoindenter elastic modulus of the pressure-sensitive adhesive layer at 25°C is preferably 0.4 MPa or more, more preferably 0.5 MPa or more, and even more preferably 0.8 MPa or more. Within such a range, the transferability is improved when transferring an electronic component from a predetermined member (e.g., a sapphire substrate) to the pressure-sensitive adhesive sheet and allowing the pressure-sensitive adhesive sheet to receive the electronic component. In this way, a pressure-sensitive adhesive sheet with excellent transferability when receiving an electronic component is particularly useful in a process (e.g., a PSLLO process) in which only a portion of a plurality of electronic components arranged on a predetermined member is selectively received by the pressure-sensitive adhesive sheet.
[0022] The pressure-sensitive adhesive layer has a normal storage modulus at 25° C. of preferably 10 MPa or less, more preferably 5 MPa or less, and further preferably 0.01 MPa to 3 MPa. The term "normal storage modulus" refers to the modulus of elasticity before irradiation with active energy rays. The method for measuring the storage modulus will be described later.
[0023] The adhesive layer has a resistance of 460 mJ / cm 2 The tensile modulus at 25° C. after irradiation with ultraviolet light is preferably 0.05 MPa to 100 MPa, and more preferably 0.1 MPa to 70 MPa. The method for measuring the tensile modulus will be described later.
[0024] The thickness of the pressure-sensitive adhesive layer is preferably 1.5 μm to 50 μm, more preferably 2.1 μm to 35 μm, and even more preferably 3 μm to 30 μm. Within such a range, the electronic components as the adherends are appropriately embedded in the pressure-sensitive adhesive layer, and a pressure-sensitive adhesive sheet having excellent fixation properties (i.e., receiving properties) and peeling properties (i.e., delivery properties) can be obtained.
[0025] In one embodiment, the thickness of the adhesive layer is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. By reducing the thickness of the adhesive layer, the transferability is improved when transferring an electronic component from a predetermined member (e.g., a sapphire substrate) to an adhesive sheet and allowing the adhesive sheet to receive the electronic component. In this way, an adhesive sheet with excellent transferability when receiving an electronic component is particularly useful in a process (e.g., a PSLLO process) in which only a portion of electronic components arranged on a predetermined member are selectively received by the adhesive sheet.
[0026] The normal probe tack value of the pressure-sensitive adhesive layer is preferably 8 N / cm 2 More preferably, it is 12 N / cm 2 More preferably, it is 15 N / cm 2Within this range, a pressure-sensitive adhesive sheet having excellent fixability for electronic components can be obtained. The upper limit of the normal probe tack value of the pressure-sensitive adhesive layer is, for example, 60 N / cm 2 The method for measuring the probe tack value will be described later. The term "normal probe tack value" refers to the probe tack value before irradiation with active energy rays.
[0027] The adhesive layer has a resistance of 460 mJ / cm 2 The probe tack value after exposure to UV light is 15N / cm 2 It is preferable that the resistance is less than 12N / cm 2 It is more preferable that the thickness is within the following range: Within such a range, a pressure-sensitive adhesive sheet having excellent releasability can be obtained.
[0028] (Active energy ray curable adhesive) As described above, the pressure-sensitive adhesive layer contains an active energy ray-curable pressure-sensitive adhesive.
[0029] Examples of the base polymer constituting the pressure-sensitive adhesive include acrylic polymers, rubber polymers (e.g., natural rubber, chloroprene rubber, styrene-butadiene rubber, nitrile rubber, etc.), polyesters, urethane polymers, polyethers, silicone polymers, polyamides, fluorine-based polymers, ethylene-vinyl acetate polymers, epoxy resins, vinyl chloride polymers, cyanoacrylate polymers, cellulose polymers (nitrocellulose polymers, etc.), phenolic resins, polyimides, polyolefins, styrene polymers, polyvinyl acetate, polyvinyl alcohol, polyvinyl acetal, polyvinyl pyrrolidone, polyvinyl butyral, polybenzimidazole, melamine resins, urea resins, and resorcinol polymers. These polymers may be used alone or in combination of two or more. From the viewpoints of adhesion, cost, etc., acrylic polymers and rubber polymers are preferred, and acrylic polymers are more preferred. The term "base polymer" refers to the main component of the polymer contained in the pressure-sensitive adhesive. The polymer is preferably a rubber-like polymer that exhibits rubber elasticity in a temperature range around room temperature. In this specification, unless otherwise specified, the term "main component" refers to a component contained in an amount of more than 50% by weight.
[0030] The acrylic polymer is preferably, for example, a polymer of a monomer raw material containing an alkyl (meth)acrylate as a main monomer and a sub-monomer copolymerizable with the main monomer. Here, the main monomer refers to a component that accounts for more than 50% by weight of the monomer composition in the monomer raw material. The content of the main monomer is preferably 60 parts by weight to 100 parts by weight, more preferably 70 parts by weight to 99.5 parts by weight, based on 100 parts by weight of the total amount of monomers in the monomer raw material.
[0031] As the alkyl(meth)acrylate, for example, a compound represented by the following formula (1) can be suitably used. CH2=C(R 1 )COOR 2 (1) Here, R in the above formula (1) 1is a hydrogen atom or a methyl group. 2 R is a branched or linear alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms may be referred to as "C1-20"). 2 is preferably a branched or linear C1-14 alkyl group, more preferably a branched or linear C6-14 alkyl group, and even more preferably a branched or linear C8-12 alkyl group.
[0032] Specific examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and isooctyl (meth)acrylate. ) acrylate, nonyl (meth) acrylate, isononyl (meth) acrylate, decyl (meth) acrylate, isodecyl (meth) acrylate, undecyl (meth) acrylate, lauryl (meth) acrylate, tridecyl (meth) acrylate, tetradecyl (meth) acrylate, pentadecyl (meth) acrylate, hexadecyl (meth) acrylate, heptadecyl (meth) acrylate, octadecyl (meth) acrylate, nonadecyl (meth) acrylate, eicosyl (meth) acrylate, etc. These alkyl (meth) acrylates can be used alone or in combination of two or more. Among them, 2-ethylhexyl acrylate (2EHA) and lauryl (meth) acrylate (LA, LMA) are preferred.
[0033] In one embodiment, R 2In the present invention, an alkyl (meth)acrylate is used, in which R is a branched or linear alkyl group having 8 or more carbon atoms. By using such a monomer as the main monomer, it is possible to obtain a pressure-sensitive adhesive sheet that has a preferable elastic modulus before and after curing and is particularly excellent in the fixing property and peeling property of electronic components. 2 Examples of alkyl(meth)acrylates in which R is a branched or linear alkyl group having 8 or more carbon atoms include 2EHA, octyl(meth)acrylate, isooctyl(meth)acrylate, nonyl(meth)acrylate, isononyl(meth)acrylate, decyl(meth)acrylate, isodecyl(meth)acrylate, and dodecyl(meth)acrylate. 2 The content of the structural unit derived from alkyl (meth)acrylate, which is a branched or linear alkyl group having 8 or more carbon atoms, is preferably 60 parts by weight to 100 parts by weight, and more preferably 70 parts by weight to 95 parts by weight, per 100 parts by weight of the base polymer.
[0034] The secondary monomer having copolymerizability with the main monomer alkyl (meth)acrylate can be useful for introducing crosslinking points into the acrylic polymer or for increasing the cohesive strength of the acrylic polymer. It is also preferable to adopt a monomer having a functional group (functional group a) capable of reacting with the functional group (functional group b) of the carbon-carbon double bond-containing monomer described below as the secondary monomer. As the secondary monomer, for example, the following functional group-containing monomer components can be used alone or in combination of two or more. Carboxy group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), crotonic acid, etc.; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, citraconic acid, etc., and their anhydrides (maleic anhydride, itaconic anhydride, etc.); Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether; Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate; Epoxy group-containing monomers: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether; Cyano group-containing monomers: for example acrylonitrile, methacrylonitrile; Keto group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate; Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine; Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane; Isocyanate group-containing monomers: (meth)acryloyl isocyanate, 2-(meth)acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate. From the viewpoint of maintaining releasability, it is preferable not to use an amide group-containing monomer that can generate a polymer having high affinity with metals.
[0035] In one embodiment, as the secondary monomer, a hydroxyl group-containing monomer is preferably used, and 2-hydroxyethyl (meth)acrylate is more preferably used. By using this monomer, a pressure-sensitive adhesive sheet having a preferable elastic modulus before and after curing and particularly excellent fixing property and peeling property of electronic components can be obtained.
[0036] The content of the structural unit derived from the secondary monomer is preferably 0.1 to 40 parts by weight, and more preferably 1 to 30 parts by weight, relative to 100 parts by weight of the base polymer. Within this range, a pressure-sensitive adhesive layer having high cohesive strength and excellent adhesiveness can be formed.
[0037] In addition, when a base polymer having a carbon-carbon double bond is used as the base polymer, it is preferable to use a sub-monomer having a functional group (functional group a) that can react with a functional group (functional group b) of a compound B having a carbon-carbon double bond, which will be described later, as the sub-monomer. In such a case, the type of the sub-monomer is determined by the type of compound B. As the sub-monomer having the functional group a, for example, a carboxyl group-containing monomer, an epoxy group-containing monomer, a hydroxyl group-containing monomer, or an isocyanate group-containing monomer is preferable, and a hydroxyl group-containing monomer is particularly preferable. By using a hydroxyl group-containing monomer as the sub-monomer, the acrylic polymer has a hydroxyl group. On the other hand, by using an isocyanate group-containing monomer as the compound B having a carbon-carbon double bond, the hydroxyl group of the acrylic polymer reacts with the isocyanate group of the compound, and the carbon-carbon double bond derived from the compound B is introduced into the acrylic polymer.
[0038] For the purpose of increasing the cohesive strength of the acrylic polymer, copolymerization components other than the above-mentioned secondary monomers may be used. Examples of such copolymerization components include vinyl ester monomers such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.), and vinyl toluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl di(meth)acrylate, and isobornyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as aryl (meth)acrylates (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (e.g., phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylates (e.g., benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and the like. The copolymerization components other than these sub-monomers may be used alone or in combination of two or more. The amount of such other copolymerization components is, for example, 2 to 20 parts by weight based on 100 parts by weight of the total amount of monomers in the monomer raw material.
[0039] Furthermore, for the purpose of crosslinking the acrylic polymer, a polyfunctional monomer can be used as a copolymerizable component. As the polyfunctional monomer, one or more of hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, etc. can be used. The amount of the polyfunctional monomer is, for example, 30 parts by weight or less with respect to 100 parts by weight of the total amount of monomers in the monomer raw material.
[0040] The acrylic polymer can be obtained by any appropriate polymerization method, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and the like.
[0041] Preferably, a carbon-carbon double bond is introduced into the base polymer (preferably an acrylic polymer). By using a base polymer having a carbon-carbon double bond, a pressure-sensitive adhesive layer that is cured by active energy rays (typically ultraviolet rays) can be formed. In addition to the above method, in the present invention, a curable pressure-sensitive adhesive layer can also be formed using a pressure-sensitive adhesive containing a polymerizable monomer or oligomer and an acrylic polymer. However, from the viewpoint of obtaining a pressure-sensitive adhesive sheet with excellent releasability, it is preferable to form a curable pressure-sensitive adhesive layer using a base polymer having a carbon-carbon double bond.
[0042] Any suitable method can be adopted as a method for producing a base polymer having a carbon-carbon double bond. For example, a method can be mentioned in which a polymer A having a functional group a is reacted with a compound B having a functional group (functional group b) that can react with the functional group a and a carbon-carbon double bond. In this case, it is preferable to carry out the reaction so that the carbon-carbon double bond does not disappear, and for example, a condensation reaction, an addition reaction, etc. can be adopted. For example, as described above, a polymer obtained by copolymerizing an alkyl (meth)acrylate as a main monomer and a sub-monomer having a functional group a is used as the polymer A.
[0043] The combination of the functional group a and the functional group b includes a combination of a carboxy group and an epoxy group, a combination of a carboxy group and an aziridyl group, a combination of a hydroxyl group and an isocyanate group, etc. Among them, from the viewpoint of reaction tracing, a combination of a hydroxyl group and an isocyanate group is preferred. From the viewpoint of polymer design, etc., a combination in which the acrylic polymer has a hydroxyl group and the above compound has an isocyanate group is particularly preferred.
[0044] Examples of the compound having the carbon-carbon double bond and the functional group b include isocyanate group-containing monomers (isocyanate group-containing compounds). Among them, 2-(meth)acryloyloxyethyl isocyanate is more preferred.
[0045] The amount of the isocyanate group-containing monomer is preferably 1 to 40 parts by weight, more preferably 5 to 30 parts by weight, and even more preferably 8 to 15 parts by weight, relative to 100 parts by weight of the polymer before the carbon-carbon double bond is introduced (i.e., polymer A).
[0046] Alternatively, a carbon-carbon double bond may be introduced so that the hydroxyl group of the polymer A remains. In this way, the degree of crosslinking can be increased when the pressure-sensitive adhesive layer is heated. In this case, the molar ratio (a / b) of the hydroxyl group as the functional group a to the isocyanate group as the functional group b is suitably more than 1, and preferably 1.1 or more.
[0047] The weight average molecular weight Mw of the base polymer (preferably an acrylic polymer) is preferably 10×10 4 ~500×10 4 and more preferably 20×10 4 ~200×10 4 and more preferably 30×10 4 ~100×10 4 Within such a range, a pressure-sensitive adhesive layer with little adhesive residue and excellent adhesion can be formed. In this specification, Mw refers to a value calculated in terms of standard polystyrene obtained by GPC.
[0048] Preferably, the pressure-sensitive adhesive contains a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, and amine-based crosslinking agents. These crosslinking agents can be used alone or in combination of two or more.
[0049] The content of the crosslinking agent is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 8 parts by weight, relative to 100 parts by weight of the base polymer of the adhesive. Within this range, an adhesive layer with an appropriately adjusted nanoindenter elastic modulus can be formed.
[0050] In one embodiment, an isocyanate-based crosslinking agent is preferably used. The isocyanate-based crosslinking agent is preferred because it can react with various functional groups. Specific examples of the isocyanate-based crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). Preferably, a crosslinking agent having three or more isocyanate groups is used.
[0051] The isocyanate crosslinking agent is preferably added so that the number of functional groups of the isocyanate crosslinking agent is 10 mol% to 50 mol%, more preferably 20 mol% to 40 mol%, based on the number of functional groups in the base polymer that can react with the isocyanate crosslinking agent. By adding the isocyanate crosslinking agent in such an amount, a pressure-sensitive adhesive layer having an appropriately adjusted nanoindenter elastic modulus can be formed.
[0052] The pressure-sensitive adhesive may further contain any suitable additives as necessary, such as photopolymerization initiators, tackifiers, plasticizers (e.g., trimellitic acid ester-based plasticizers, pyromellitic acid ester-based plasticizers), pigments, dyes, fillers, antioxidants, conductive materials, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, solvents, etc.
[0053] C. Base material The substrate may be made of any suitable resin, such as polyolefin resins, such as polyethylene resins, polypropylene resins, polybutene resins, and polymethylpentene resins, polyurethane resins, polyester resins, polyimide resins, polyether ketone resins, polystyrene resins, polyvinyl chloride resins, polyvinylidene chloride resins, fluorine resins, silicone resins, cellulose resins, and ionomer resins.
[0054] In one embodiment, a substrate made of a polyester resin is used as the substrate. Substrates made of polyester resin preferably have rigidity, and the use of such a substrate can prevent displacement of an electronic component when it is fixed.
[0055] The thickness of the substrate is preferably from 2 μm to 300 μm, more preferably from 5 μm to 200 μm, and further preferably from 10 μm to 200 μm.
[0056] In one embodiment, a substrate having a thickness of 30 μm to 200 μm (preferably a substrate made of a polyester resin) is used. By using a substrate with such a thickness, it is possible to prevent displacement when fixing an electronic component.
[0057] D. Another adhesive layer The separate adhesive layer may be composed of any suitable adhesive. The adhesive may be a curable adhesive or a pressure-sensitive adhesive. The separate adhesive layer may include, for example, an acrylic adhesive, a rubber adhesive, a silicone adhesive, or the like.
[0058] The thickness of the another pressure-sensitive adhesive layer is, for example, 1 μm to 100 μm.
[0059] E. Manufacturing method of adhesive sheet The pressure-sensitive adhesive sheet can be produced by any suitable method. The pressure-sensitive adhesive sheet can be obtained, for example, by coating the pressure-sensitive adhesive on a substrate. As a coating method, various methods can be adopted, such as bar coater coating, air knife coating, gravure coating, gravure reverse coating, reverse roll coating, lip coating, die coating, dip coating, offset printing, flexographic printing, and screen printing. In addition, a method of forming a pressure-sensitive adhesive layer on a release liner and then laminating it to a substrate can also be adopted.
[0060] F. How to use adhesive sheets (electronic component processing methods) The pressure-sensitive adhesive sheet of the present invention can be used when transferring an electronic component between members in any appropriate processing step of the electronic component. For example, in one embodiment, a processing method of an electronic component using the pressure-sensitive adhesive sheet is provided, and the processing method includes (a) step a of transferring the electronic component arranged on a first member onto the adhesive layer of the pressure-sensitive adhesive sheet (the pressure-sensitive adhesive sheet receives the electronic component), and (b) step b of picking up the electronic component with a second member and peeling the electronic component from the pressure-sensitive adhesive sheet (the pressure-sensitive adhesive sheet delivers the electronic component). Any appropriate processing step can be performed before step a, between steps a and b, and after step b.
[0061] In one embodiment, a plurality of the electronic components are arranged on the first member. In one embodiment, in the step a, all of the electronic components arranged on the first member are transferred onto the adhesive sheet. In another embodiment, a portion of the electronic components arranged on the first member are selectively transferred onto the adhesive sheet.
[0062] In one embodiment, step b includes step b-1 of contacting the second member with the electronic component on the adhesive layer, step b-2 of irradiating the adhesive sheet (substantially the adhesive layer) with active energy rays, and step b-3 of picking up the electronic component with the second member and peeling the electronic component from the adhesive sheet.
[0063] In one embodiment, the electronic component may be an LED. In one embodiment, a mini LED or a micro LED may be used as the LED. A mini LED is, for example, an LED chip with a side of 100 μm or more, and a growth support substrate such as a sapphire substrate adjacent to a light emitting (epitaxial) layer mainly made of gallium nitride. In this specification, even if a side is 100 μm or less, an LED chip having a growth support substrate such as a sapphire substrate is defined as a mini LED. A side of a mini LED chip is, for example, 50 μm to 500 μm, and a thickness is, for example, 30 μm to 200 μm. A micro LED is, for example, an LED chip with a side of 100 μm or less, and a light emitting (epitaxial) layer mainly made of gallium nitride is separated from a growth support substrate such as a sapphire substrate, and has a structure consisting of only the light emitting (epitaxial) layer. In this specification, an LED chip that does not have a growth support substrate such as a sapphire substrate is defined as a micro LED even if one side is 100 μm or more. One side of the micro LED chip is, for example, 5 μm to 200 μm, and the thickness is, for example, 3 μm to 30 μm.
[0064] In one embodiment, the electronic component is an LED (preferably, a micro LED), and the first member is a sapphire substrate. In such an embodiment, in step a, the sapphire substrate on which the LED is arranged is irradiated with UV laser light, and the LED is transferred to the adhesive sheet. Here, the LED is peeled off from the sapphire substrate by chemically decomposing the interface between the sapphire substrate and the LED by irradiating with UV laser light. Specifically, gallium nitride present in the vicinity of the interface between the sapphire substrate and the LED is decomposed into liquid metal gallium and gaseous nitrogen by irradiating with UV laser light, and the LED is separated from the sapphire substrate. In one embodiment, all the LEDs arranged on the sapphire substrate are transferred onto the adhesive sheet. In another embodiment, a part of the LEDs arranged on the sapphire substrate is selectively transferred onto the adhesive sheet. EXAMPLES
[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Test and evaluation methods in the examples are as follows. Furthermore, unless otherwise specified, "parts" and "%" are by weight.
[0066] (1) Nanoindenter Elastic Modulus Using a nanoindenter (manufactured by Hysitron Inc., product name "Triboindenter TI-950"), a single indentation method was performed at a specified temperature (25°C) under the measurement conditions of an indentation speed of about 500 nm / sec, an extraction speed of about 500 nm / sec, and an indentation depth of about 3000 nm, with an intensity of 460 mJ / cm 2 The elastic modulus of the pressure-sensitive adhesive layer surface after irradiation with ultraviolet light was measured.
[0067] (2) Storage modulus of adhesive layer in normal state Using a dynamic viscoelasticity measuring device (manufactured by TA instruments, product name "ARES-G2"), the storage modulus G' and loss factor tanδ were measured at a measurement frequency of 1 Hz, strain of 0.05%, and 25°C. Specifically, a 50 μm thick adhesive sheet without a substrate was prepared using the normal adhesive obtained in the examples and comparative examples, and the adhesive sheet was laminated to a thickness of 1.0 mm or more, punched out to a φ8 mm size using a jig, and set on the ARES-G2 probe. Measurements were performed at a temperature rise rate of 5°C / min from -50°C to 200°C. The value of the storage modulus G' at 25°C was extracted from the obtained data.
[0068] (3) 460 mJ / cm 2 Tensile modulus of adhesive layer after exposure to ultraviolet light A dynamic viscoelasticity measuring device (manufactured by TA Instrument, product name "RSA-3") was used to measure the tensile modulus E' at a measurement frequency of 1 Hz, a strain of 0.05%, and 25°C. Specifically, a 50 μm thick adhesive sheet without a substrate was produced using the adhesives obtained in the Examples and Comparative Examples, and the adhesive sheet was laminated to a thickness of 200 μm or more. With release liners attached to both sides of the sample, a tensile modulus E' of 460 mJ / cm2 After irradiating each side with ultraviolet light once, the release liner was removed and the adhesive layer was prepared into a 10 mm wide sample. The chuck distance was 20 mm, and the temperature was increased from 0°C to 200°C at a rate of 5°C / min. From the obtained data, the tensile modulus E' at 25°C was extracted.
[0069] (4) Probe Tack The entire surface of the adhesive sheet (width 20 mm × length 50 mm) opposite the adhesive layer to be evaluated was attached to a slide glass (manufactured by Matsunami Glass Industry Co., Ltd., 26 mm × 76 mm) using a 2 kg hand roller via double-sided adhesive tape (Nitto Denko Corporation, product name "No. 5600"). Then, the probe tack value of the exposed adhesive layer surface and the 460 mJ / cm2 of the exposed adhesive layer surface were measured. 2 The probe tack value after irradiation with ultraviolet light was measured using a probe tack measuring device (manufactured by RHESCA, product name "TACKINESS Model TAC-II") with a 5 mmφ SUS probe terminal under the conditions of probe descent speed (immersion speed): 120 mm / min, test speed (test speed): 600 mm / min, contact load (Preload): 20 gf, and contact retention time (press time): 1 second. The measurement was performed with N=5, and the average of these measured values was taken as the probe tack value. In addition, the pressure-sensitive adhesive sheets of Examples 17 to 22 were attached to the slide glass with a 2 kg hand roller on the pressure-sensitive adhesive surface opposite to the pressure-sensitive adhesive layer of the evaluation surface, and the probe tack value was measured under the same conditions as above.
[0070] (5) Adhesive strength The adhesive layer of the adhesive sheet was attached to SUS304BA, and the adhesive strength of the adhesive sheet to the adhesive sheet was measured by a method conforming to JIS Z 0237:2000 (lamination conditions: 1 round trip with a 2 kg roller, tensile speed: 300 mm / min, peel angle 180°, measurement temperature: 23°C). In addition, the adhesive layer of the adhesive sheet was attached to a polyethylene terephthalate film (manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness: 25 μm), and the adhesive strength of the adhesive sheet to the polyethylene terephthalate film was measured by peeling the adherend from the adhesive sheet by a method conforming to JIS Z 0237:2000 (lamination conditions: 1 round trip with a 2 kg roller, tensile speed: 300 mm / min, peel angle 180°, measurement temperature: 23°C). After the adhesive was applied to the adherend as described above, the adhesive layer was subjected to a 460 mJ / cm 2 The adhesive strength after irradiation with ultraviolet light was measured by the above method.
[0071] (6) TMA sinking depth Using a thermomechanical analyzer (manufactured by TA-instrument, product name "TMA Q400") and a φ1.0 mm probe, the sinking depth of the adhesive sheet was measured from the adhesive layer side in the penetration mode under the following conditions: nitrogen gas flow rate: 50.0 ml / min, indentation load: 0.5 N, measurement atmosphere temperature: 40° C., indentation load time: 20 min. Measurements were performed with N=5, and the average value of N=3 excluding the maximum and minimum values among these measurements was taken as the sinking depth of the sample.
[0072] (7) Chip embeddability during bonding When the sinking depth of the adhesive sheet measured by thermomechanical analysis (TMA) is 3 μm or more and less than 27 μm, the embeddability is excellent (marked with a circle in the table); when it is 27 μm or more, the embeddability is excessive (marked with an x in the table).
[0073] (8) Deformation of the substrate The deformation amount of the substrate was calculated by subtracting the thickness of the adhesive layer of the adhesive sheet from the sinking depth of the adhesive sheet measured by thermomechanical analysis (TMA). When the sinking depth of the adhesive sheet was smaller than the thickness of the adhesive layer, it was considered that there was no deformation of the substrate.
[0074] (9) Tip position accuracy When the deformation amount of the substrate calculated from the sinking depth of the adhesive sheet measured by thermomechanical analysis (TMA) is less than 20 μm, the positional accuracy when receiving the chip is excellent (◯ in the table); when it is 20 μm or more, the positional accuracy when receiving the chip is insufficient (× in the table).
[0075] (10) 460 mJ / cm 2 Shear adhesive strength after exposure to ultraviolet light The adhesive sheets (size: 20 mm x 20 mm) obtained in the examples and comparative examples were attached and fixed on a predetermined base (e.g., 26 mm x 76 mm slide glass manufactured by Matsunami Glass Industry Co., Ltd.) on the side opposite to the adhesive layer, and a 1 mm x 1 mm silicon chip was placed on the adhesive layer surface of the adhesive sheet, and the silicon chip was thermocompressed for 1 minute using a heat press machine under lamination conditions of 40°C and 0.05 MPa to prepare an evaluation sample. Note that a double-sided adhesive tape (Nitto Denko Corporation, product name "No. 5600") was used to fix the adhesive sheet without a separate adhesive layer to the base. Using an ultraviolet irradiation device (manufactured by Nitto Seiki Co., Ltd., product name "UM-810"), ultraviolet light (characteristic wavelength: 365 nm, accumulated light amount: 460 mJ / cm) from a high-pressure mercury lamp was applied from the predetermined base side of the obtained evaluation sample. 2 , Irradiation energy: 70W / cm 2 The adhesive layer of the adhesive sheet with the silicon chip attached was irradiated with light (irradiation time: 6.6 seconds) to prepare a sample for evaluation. For the evaluation sample, at an environmental temperature of 25°C, a Nordson dage4000 was used to set a measurement terminal on the side of a 1 mm x 1 mm silicon chip at a height of 50 μm from the attachment surface, and an external force was applied horizontally to the chip at a shear rate of 500 μm / sec., from which the maximum breaking load was read from the load-displacement curve obtained, and this was taken as the shear adhesive strength at an environmental temperature of 25°C. Measurements were performed with N=5, and the average value of N=3 excluding the maximum and minimum values among these measured values was taken as the shear adhesive strength of the sample.
[0076] (11) Transferability 460mJ / cm 2 The shear adhesive strength after exposure to ultraviolet light is 2000N / cm 2 If the resistance is less than 2000N / cm, the transferability is excellent when transferring the chip (marked as ◯ in the table). 2 More than 2400N / cm 2 When the transferability is less than 2400N / cm, the transferability when transferring the chip is good (△ in the table), and 2 If the value is more than this, the transferability when transferring the chip is insufficient (marked with x in the table).
[0077] [Production Example 1] Preparation of Acrylic Polymer A 88.8 parts by weight of 2-ethylhexyl acrylate (2-EHA), 11.2 parts by weight of hydroxyethyl acrylate (HEA), 0.2 parts by weight of a polymerization initiator (manufactured by NOF Corporation, trade name "Niper BW"), and toluene were mixed. The resulting mixture was polymerized at 60°C under a nitrogen gas stream to obtain an acrylic copolymer with a weight average molecular weight (Mw) of approximately 600,000. To a toluene solution containing 100 parts by weight of an acrylic copolymer, 12 parts by weight of methacryloyloxyethyl isocyanate (MOI) and 0.06 parts by weight of butyltin dilaurate were added to cause an addition reaction of the MOI to prepare an acrylic polymer A having a carbon-carbon double bond.
[0078] [Production Example 2] Preparation of Acrylic Polymer B 91 parts by weight of lauryl methacrylate (LMA), 9.3 parts by weight of 2-ethylhexyl methacrylate (2-HEMA), 0.2 parts by weight of a polymerization initiator (manufactured by NOF Corporation, trade name "Niper BW"), and toluene were mixed. The resulting mixture was polymerized at 60°C under a nitrogen gas flow to obtain an acrylic copolymer. To a toluene solution containing 100 parts by weight of an acrylic copolymer, 9.1 parts by weight of methacryloyloxyethyl isocyanate (MOI) and 0.04 parts by weight of butyltin dilaurate were added to cause an addition reaction of the MOI to prepare an acrylic polymer B having a carbon-carbon double bond.
[0079] [Production Example 3] Preparation of Acrylic Polymer C 100 parts by weight of 2-ethylhexyl acrylate (2-EHA), 25.5 parts by weight of acryloylmorpholine (ACMO), 18.5 parts by weight of hydroxyethyl acrylate (HEA), 0.2 parts by weight of a polymerization initiator (manufactured by NOF Corporation, trade name "Niper BW"), and toluene were mixed. The resulting mixture was polymerized at 60°C under a nitrogen gas stream to obtain an acrylic copolymer with a weight average molecular weight (Mw) of about 900,000. To a toluene solution containing 100 parts by weight of an acrylic copolymer, 8.5 parts by weight of methacryloyloxyethyl isocyanate (MOI) and 0.04 parts by weight of butyltin dilaurate were added to cause an addition reaction of the MOI to prepare an acrylic polymer C having a carbon-carbon double bond.
[0080] [Production Example 4] Preparation of Acrylic Polymer D 75 parts by weight of 2-ethylhexyl acrylate (2-EHA), 15 parts by weight of acryloylmorpholine (ACMO), 22 parts by weight of hydroxyethyl acrylate (HEA), 0.2 parts by weight of a polymerization initiator (manufactured by NOF Corporation, trade name "Niper BW"), and toluene were mixed. The resulting mixture was polymerized at 60°C under a nitrogen gas flow to obtain an acrylic copolymer. To a toluene solution containing 100 parts by weight of an acrylic copolymer, 17.7 parts by weight of methacryloyloxyethyl isocyanate (MOI) and 0.04 parts by weight of butyltin dilaurate were added to cause an addition reaction of the MOI to prepare an acrylic polymer D having a carbon-carbon double bond.
[0081] [Production Example 5] Preparation of Acrylic Polymer E 50 parts by weight of butyl acrylate (BA), 39 parts by weight of ethyl acrylate (EA), 20 parts by weight of hydroxyethyl acrylate (HEA), 0.3 parts by weight of a polymerization initiator (manufactured by NOF Corporation, product name "Niper BW"), and toluene were mixed. The resulting mixture was polymerized at 60°C under a nitrogen gas flow to obtain an acrylic copolymer. To a toluene solution containing 100 parts by weight of an acrylic copolymer, 19.5 parts by weight of methacryloyloxyethyl isocyanate (MOI) and 0.06 parts by weight of butyltin dilaurate were added to cause an addition reaction of the MOI to prepare an acrylic polymer E having a carbon-carbon double bond.
[0082] [Production Example 6] Preparation of Acrylic Polymer F 30 parts by weight of 2-ethylhexyl acrylate (2-EHA), 70 parts by weight of methyl acrylate (MA), 10 parts by weight of acrylic acid (AA), 0.4 parts by weight of a polymerization initiator (manufactured by NOF Corporation, product name "Niper BW"), and toluene were mixed and then heated at 70°C to prepare a toluene solution of an acrylic copolymer (acrylic polymer F).
[0083] [Example 1] To the toluene solution of the acrylic polymer A, 3 parts by weight of an isocyanate crosslinking agent (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L") and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "Omnirad127": 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one) were added per 100 parts by weight of the solid content of the acrylic polymer to prepare an adhesive. The adhesive was applied to one side of a PET substrate (100 μm, "Lumirror S1N" manufactured by Toray Industries, Inc.) to obtain an adhesive sheet A (adhesive layer / PET substrate) having an ultraviolet-curable adhesive layer (thickness: 2 μm). The resulting pressure-sensitive adhesive sheet A was subjected to the above-mentioned evaluations, and the results are shown in Table 1.
[0084] [Examples 2 to 16, Example 23, Comparative Examples 1 to 3] An adhesive sheet was obtained in the same manner as in Example 1, except that the acrylic polymer, crosslinking agent, tackifier, and photopolymerization initiator shown in Table 1 were used in the amounts shown in Tables 1 and 2, and the base material shown in Table 1 was used. The adhesive sheet obtained was subjected to the above-mentioned evaluations. The results are shown in Tables 1 and 2. The compounds used in the examples and comparative examples are as follows. "YS Polystar S145": Terpene phenol-based tackifier, manufactured by Yasuhara Chemical Co., Ltd. "UV-1700": Active energy ray curable oligomer (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "Shikou UV-1700B") "Omnirad651": BASF product name "Omnirad 651" "PET (printed product)": PET film manufactured by Daisanshi Co., Ltd. (thickness: 50 μm, light red solid print) "PO": A base material obtained by feeding a propylene-based thermoplastic elastomer containing a propylene component and an ethylene propylene rubber component (manufactured by Mitsubishi Chemical Corporation, product name "Zelas") into a T-die molding machine (set temperature: 230°C) manufactured by Blaco, and molding it into a film having a thickness of 80 μm.
[0085] [Example 17] An adhesive sheet i (adhesive layer / PET substrate) was obtained in the same manner as in Example 1, except that the acrylic polymer, crosslinking agent, tackifier, and photopolymerization initiator shown in Table 1 were used in the amounts shown in Table 1. A coating liquid was prepared by adding 0.6 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Company, product name "Tetrad C") to a toluene solution containing 100 parts by weight of acrylic polymer G (a copolymer of 95 parts by weight of 2-ethylhexyl acrylate (2-EHA) and 5 parts by weight of acrylic acid (AA)). The coating liquid was applied to the surface of the PET substrate of the above-mentioned adhesive sheet i opposite to the adhesive layer to obtain an adhesive sheet I (adhesive layer / PET substrate / another adhesive layer (thickness: 30 μm)). The obtained adhesive sheet was subjected to the above-mentioned evaluations. The results are shown in Table 3.
[0086] [Examples 18 to 22] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 17, except that a substrate having a thickness shown in Tables 3 and 4 was used. The pressure-sensitive adhesive sheet obtained was subjected to the above-mentioned evaluations. The results are shown in Tables 3 and 4.
[0087] [Table 1]
[0088] [Table 2]
[0089] [Table 3]
[0090] [Table 4]
[0091] 10 Base material 20 Adhesive layer 100, 200 Adhesive Sheet
Claims
1. A pressure-sensitive adhesive sheet for transferring electronic components, comprising a substrate and a pressure-sensitive adhesive layer disposed on at least one side of the substrate, The adhesive layer has a compressive strength of 460 mJ / cm 2 The nanoindenter elastic modulus at 25°C after irradiation with ultraviolet light is 500 MPa or less, The pressure-sensitive adhesive sheet for transferring electronic components has a sinking amount of 3 μm to 27 μm in a 40° C. environment using TMA. Adhesive sheet for transferring electronic components.
2. 2. The pressure-sensitive adhesive sheet for transferring electronic parts according to claim 1, wherein the pressure-sensitive adhesive layer has a thickness of 2.1 μm to 35 μm.
3. 3. The pressure-sensitive adhesive sheet for transferring electronic components according to claim 1, wherein the pressure-sensitive adhesive layer has a normal nanoindenter elastic modulus at 25°C before irradiation with active energy rays of 0.4 MPa or more.
4. The normal probe tack value of the pressure-sensitive adhesive layer before irradiation with active energy rays is 8 N / cm 2 The pressure-sensitive adhesive sheet for transferring electronic parts according to claim 1 .
5. The pressure-sensitive adhesive sheet for transferring electronic parts according to claim 1 , wherein the substrate is made of a polyester resin.
6. The pressure-sensitive adhesive sheet for transferring electronic parts according to any one of claims 1 to 5, wherein the thickness of the substrate is 30 µm to 200 µm.
7. The adhesive sheet for transferring electronic components according to claim 1 , wherein the electronic components are mini LEDs or micro LEDs.
8. The pressure-sensitive adhesive sheet for transferring electronic parts according to claim 1 , comprising the pressure-sensitive adhesive layer, the substrate, and another pressure-sensitive adhesive layer in this order.
9. A method for processing electronic parts using the pressure-sensitive adhesive sheet for transferring electronic parts according to any one of claims 1 to 8, comprising the steps of: A step a of transferring an electronic component arranged on a first member onto the adhesive layer of the adhesive sheet; and a step b of picking up the electronic component with a second member and peeling the electronic component from the adhesive sheet. Methods for processing electronic components.
10. The method for processing an electronic component according to claim 9, wherein the electronic component is a mini LED or a micro LED.
11. The step b A step b-1 of contacting the second member with the electronic component on the pressure-sensitive adhesive layer; A step b-2 of irradiating the pressure-sensitive adhesive sheet with active energy rays; and a step b-3 of picking up the electronic component with the second member and peeling the electronic component from the adhesive sheet. The method for processing an electronic component according to claim 9 or 10.
12. The method for processing an electronic component according to claim 10 or 11, wherein the first member is a sapphire substrate.
13. The electronic component is a micro LED; The method for processing electronic components according to claim 12, further comprising: irradiating the sapphire substrate on which a plurality of micro LEDs are arranged with UV laser light in the step (a) to transfer the micro LEDs to the adhesive sheet.
14. The method for processing electronic components according to claim 13 , wherein a portion of the micro LEDs arranged on the sapphire substrate is selectively transferred to the adhesive sheet.
Citation Information
Patent Citations
Transfer method, method of manufacturing image display device using the same, and transfer device
JP2020053558A